O cristianismo e o inimigo islâmico a partir de Eulógio: o legado do martírio cordobês e a formação de um mito político - Rocha, Augusto Machado (2021)
Based on the writings of Eulogius, between the years 851 and 857, in Cordova, in the Al-Andalus, we will analyze the process that generated the representation of Muslim culture as vile. Such representation would have been centered on the figure of an evil man, the Prophet Muhammad. Our aim is to understand how this perspective has expanded, in a way it still impacts the present. For the development of this research, the concepts of martyrdom, representation and political myth were essential. The first chapter focuses on how Saint Eulogius sought to introduce the hagiography of martyrs, from the perspective of heroes before the enemy. In the sequence we have analyzed the way in which Eulogius presented the Other that afflicted him, through the proposed delimitation of the figure of the Muslim enemy, using the Prophet as a central element. Finally, in the third chapter, the role of Eulógio for the formation of a political myth referring to Islam was shown, as well as its possible connection to the perception of the anti-Islamic controversy. In our analysis, we seek to define how the political myth concerning Islam can find one of its bases in the arguments proposed by this Cordovan author, when focusing on his original speech, the Documentum Martiriale (851), the Memoriale Sanctorum (851 - 857) and final text, Apologeticum Martirium (857).